Do we need to categorize it? Reflections on constituencies and quotas as tools for negotiating difference in the global food sovereignty convergence space. Issue 7 (10th November 2019) - Claeys, Priscilla; Duncan, Jessica
ABSTRACT: Convergence – as an objective and as a process – designates the coming together of different social actors across strategic, political, ideological, sectoral and geographic divides. In this paper, we analyze the global food sovereignty movement (GFSM) as a convergence space, with a focus on constituencies and quotas as tools to maintain diversity while facilitating convergence. We show how the use of constituencies and quotas has supported two objectives of the GFSM: alliances building and effective direct representation in global policy-making spaces. We conclude by pointing to some convergence challenges the GFSM faces as it expands beyond its agrarian origins.